This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Physics 315: Oscillations and Waves Homework 10: Solutions 1. (a) Let S = summationdisplay n =0 ,N − 1 z n = 1 + z + ··· + z N − 2 + z N − 1 . (1) It follows that z S = z + z 2 + ··· + z N − 1 + z N . (2) Thus, S − z S = 1 − z N , (3) or S = 1 − z N 1 − z . (4) (b) Let z = e i θ . It follows that S = 1 − e i N θ 1 − e i θ = e i N θ/ 2 bracketleftbig e − i N θ/ 2 − e i N θ/ 2 bracketrightbig e i θ/ 2 bracketleftbig e − i θ/ 2 − e i θ/ 2 bracketrightbig . (5) Thus, S = e i ( N − 1) θ/ 2 sin( N θ/ 2) sin( θ/ 2) . (6) since sin θ ≡ 1 2 i ( e i θ − e − i θ ) . (7) (c) Now e i n θ ≡ cos( n θ ) + i sin( n θ ) , (8) so it follows from (1) that Re ( S ) = summationdisplay n =0 ,N − 1 Re ( z n ) = summationdisplay n =0 ,N − 1 Re (e i n θ ) = summationdisplay n =0 ,N − 1 cos( n θ ) . (9) Likewise, Im( S ) = summationdisplay n =0 ,N − 1 Im (e i n θ ) = summationdisplay n =0 ,N − 1 sin( n θ ) . (10) Hence, from (6), summationdisplay n =0 ,N − 1 cos( n θ ) = cos[( N − 1) θ/ 2] sin( N θ/ 2) sin( θ/ 2) , (11) summationdisplay n =0 ,N − 1 sin( n θ ) = sin[( N − 1) θ/ 2] sin( N θ/ 2) sin( θ/ 2) . (12) Let C = summationdisplay n =1 ,N cos( α y n ) = summationdisplay n =1 ,N cos[( n − 1) α d − ( N − 1) α d/ 2] , (13) where y n = [ n − ( N + 1) / 2] d . It follows that C = cos[( N − 1) α d/ 2] summationdisplay n ′...
View
Full
Document
This note was uploaded on 11/02/2010 for the course PHY 59372 taught by Professor Fitzpatrick during the Spring '10 term at University of Texas.
 Spring '10
 Fitzpatrick
 Work

Click to edit the document details